Prevalence of feline leukemia virus and feline immunodeficiency virus in cats from southern Italy: a 10-year cross-sectional study - Fusco, Giovanna; Marati, Luisa; Pugliese, Annamaria; Levante, Martina; Ferrara, Gianmarco; de Carlo, Esterina; Amoroso, Maria Grazia; Montagnaro, Serena (Frontiers in Veterinary Science, 2023)
Introduction Feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) are well-known retroviruses causing important infections in domestic cats worldwide. The goal of this study was to determine the prevalence of FeLV and FIV infections in cat living indoor and outdoor in southern Italy. Methods The survey was conducted on 1322 stray and owned cats from the regions of Campania, Basilicata, and Calabria. It was carried out over a 10-year period to obtain a more realistic picture of the prevalence of these retroviral diseases in the country. FIV and FeLV status was determined by enzyme-linked immunosorbent assay (ELISA) using a commercial kit (SNAP Combo Plus FeLV/FIV, IDEXX). Risk factors were analysed by logistic regression. Results and Discussion The results showed that 101/1322 (7.64%) cats were positive for FeLV antigen and 110/1322 (8.32%) cats were positive for FIV antibody. Twenty-six of the 1322 cats (1.97%) were positive for both FIV and FeLV infection. Our results are similar to those published in recent studies in Europe. A statistically significant association (p < 0.05) was found between year, province, region, lifestyle and risk of FeLV infection. FIV positivity was instead statistically associated only with year and lifestyle.